1994
DOI: 10.1165/ajrcmb.11.2.8049083
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endothelial cell phospholipase D by sphingosine and sphingosine-1-phosphate.

Abstract: We have investigated the activation of phospholipase D (PLD) by sphingosine and its derivatives in bovine pulmonary artery endothelial cells (BPAEC) prelabeled with [32P]orthophosphate or [32P]lyso phospholipids. Sphingosine, in a dose- and time-dependent manner, stimulated the hydrolysis of [32P]phosphatidylcholine (PC) resulting in the production of [32P]phosphatidic acid (PA), suggesting PLD activation. In the presence of ethanol (150 mM), the accumulation of [32P]phosphatidylethanol was also observed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…Since our report of S1P-induced endothelial cell activation (16), there has been increasing evidence for a role of S1P in the maintenance and restoration of the dynamic semipermeable endothelial cellular barrier in the vasculature. S1P-mediated enhancement of endothelial junctional integrity via prominent cytoskeletal rearrangement involving the translocation of key actin-binding proteins, such as cortactin and myosin light chain kinase to the cell periphery and the formation of a strong cortical actin ring (3,5), has been defined.…”
Section: Discussionmentioning
confidence: 83%
“…Since our report of S1P-induced endothelial cell activation (16), there has been increasing evidence for a role of S1P in the maintenance and restoration of the dynamic semipermeable endothelial cellular barrier in the vasculature. S1P-mediated enhancement of endothelial junctional integrity via prominent cytoskeletal rearrangement involving the translocation of key actin-binding proteins, such as cortactin and myosin light chain kinase to the cell periphery and the formation of a strong cortical actin ring (3,5), has been defined.…”
Section: Discussionmentioning
confidence: 83%
“…These observations clearly establish that the platelet, via soluble platelet-derived factors, is essential in maintaining normal vascular homeostasis. We and others have reported on vasoactive plateletderived lipids that activate endothelium, including our first report that S1P activated EC phospholipase D (7,10,23,33,48). Subsequent studies have since demonstrated that platelet-derived phospholipids modulate the barrier function of the vascular endothelium via both endothelial barrier-perturbing lipid products such as phosphatidate (6) and barrier-stabilizing/enhancing lipid products such as lysophosphatidic acid (LPA) (8,32) and S1P (11).…”
Section: Discussionmentioning
confidence: 86%
“…S1P is a normal constituent in plasma with increased (micromolar) levels in serum that are consistent with S1P release during whole blood coagulation (51). S1P exerts diverse biological effects on cells and is now recognized as an important courier of cellular information (7,10,23,33,48). S1P stimulates proliferation, calcium mobilization, adhesion molecule expression, and suppression of caspasedependent apoptosis (7,20,40,46) via ligation of G protein-coupled receptors of the EDG family (26).…”
Section: Discussionmentioning
confidence: 99%
“…The available data indicate that endothelial cell activation induced by TNF-␣ is mediated through the generation of sphingosine 1-phospate (S1P), and S1P is able to mimic the effect of TNF-␣ on endothelial cells (30). Because S1P-mediated IL-8 secretion relies on phospholipase D (PLD)-dependent ERK activation (5,16,28) and ceramide inhibits PLD activation (9,25), it is possible that ceramide inhibits ERK phosphorylation and IL-8 secretion through PLD inhibition.…”
Section: Discussionmentioning
confidence: 99%